Instrumentos de mensuração da satisfação de pacientes atendidos por serviços de gerenciamento da terapia medicamentosa: uma revisão de escopo. - Lorayne Caroline Resende (2022)
Comprehensive Medication Management (CMM) is the service offered within the clinical practice of Pharmaceutical Care, in which the pharmacist seeks to optimize the patient's pharmacotherapy outcomes through a longitudinal and collaborative follow-up with the multi-disciplinary healthcare team. Estimating patient satisfaction is a key indicator to measure the humanistic outcomes of patient-centered services. This study aimed to map and analyze the patient satisfaction measurement instruments available for CMM services and compare them according to their developmental characteristics and applicability. The research was conducted using the Scoping Review methodology proposed by the Joanna Brigss Institute (JBI) and reported according to PRISMA Extension for Scoping Reviews (PRISMA-ScR). Were included studies that had developed or applied an instrument to measure patient satisfaction with the CMM service, published from 1990 onwards, in any setting, language, or geographic region. The search strategy was previously validated and applied in MEDLINE, Latin American and Caribbean Health Sciences Literature (LILACS), EMBASE, Cochrane, Scopus, Cinahal, and Web of Science databases, in addition to gray literature search and manual search. Comparative analysis of the instruments was performed using an 18-item checklist developed to systematically assess patient-reported outcome measures. A total of 28 studies were selected, with the majority (17) of instruments developed by the authors themselves, nine of which were validated. A predominant association of open- and closed-ended questions was observed in printed, self-administered questionnaires. In the comparative analysis, the best qualified instrument reached 11 of the 18 requirements evaluated. In general, the weaknesses of the instruments involve the difficulty to define the construct "satisfaction", the indefinition of the target population, the absence of tests to evaluate sensitivity to change, the lack of clarity to interpret the score and to manage incomplete answers, besides the absence of tests to define the required literacy level. The scoping review made it possible to identify the instruments available to measure patient satisfaction with the CMM service and compare their characteristics. Gaps were also identified that need to be considered in future research aiming to develop a robust and standardized instrument for the service.